2022
DOI: 10.1088/2634-4386/ac974d
|View full text |Cite
|
Sign up to set email alerts
|

An efficient deep neural network accelerator using controlled ferroelectric domain dynamics

Abstract: The current work reports an efficient deep neural network (DNN) accelerator where analog synaptic weight elements are controlled by ferroelectric domain dynamics. An integrated device-to-algorithm framework for benchmarking novel synaptic devices is used. In P(VDF-TrFE) based ferroelectric tunnel junctions, analog conductance states are measured using a custom pulsing protocol and associated control circuits and array architectures for DNN training is simulated. Our results show precise control of polarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…[ 5 ] In our previous work, we have shown that it is challenging to obtain a large dynamic conductance range ( G max /G min ) in FTJ devices with NLS domain switching characteristics, with programming pulses of 1 V magnitude and ns durations. [ 14 ] In comparison, FeFETs show a much higher G max /G min ratio due to the large On/Off ratio of the FETs. However, the entire dynamic range cannot be used for training in most cases due to a lack of linearity and symmetry in response to potentiating and depressing pulses or due to the challenge of reading out too low current due to interfering read noise.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 5 ] In our previous work, we have shown that it is challenging to obtain a large dynamic conductance range ( G max /G min ) in FTJ devices with NLS domain switching characteristics, with programming pulses of 1 V magnitude and ns durations. [ 14 ] In comparison, FeFETs show a much higher G max /G min ratio due to the large On/Off ratio of the FETs. However, the entire dynamic range cannot be used for training in most cases due to a lack of linearity and symmetry in response to potentiating and depressing pulses or due to the challenge of reading out too low current due to interfering read noise.…”
Section: Resultsmentioning
confidence: 99%
“…International Technology Roadmap for Semiconductors (ITRS) [34] predicts that MoS 2 is a potential semiconductor material for integration into nanometer-scale structures due to outstanding electrical properties exhibited by one or few monolayer thick films. [14,15] MoS 2 or other 2D semiconductor-based circuits can provide a solution to this high operating voltage problem of the FeFETs due to an indirect bandgap of 1.2 eV of few layer MoS 2 , that resulted in transistors with a high On/Off current ratio of %10 6 -10 8 under a low operating voltage. Also, MoS 2 MOSFETs exhibited a very low SS value of 74 mV decade À1 , benefiting from the absence of dangling bonds in the MoS 2 layers.…”
Section: Doi: 101002/aisy202300391mentioning
confidence: 99%
See 1 more Smart Citation
“…Majumdar [5]: Majumdar presents an efficient deep neural network (DNN) accelerator using analog synaptic weights controlled by ferroelectric (FE) domain dynamics. They benchmark novel synaptic devices, specifically poly(vinylidene fluoride-trifluoroethylene)-based ferroelectric tunnel junctions, demonstrating their linearity in weight updates.…”
Section: Desai Et Almentioning
confidence: 99%
“…[19][20][21][22][23][24] Experiments have demonstrated the maximum number of distinct conductance levels utilized for neural-network (NN) learning for different memristive elements, e.g., resistive-switching memory (RSM) elements, magnetic-tunnelling memory (MTM) elements, ferroelectric memory (FM) elements, and other memory elements. [25][26][27] A maximum number of distinguished conductance levels used for NN learning of 2-64 has been The T material state for in situ learning. a) PCM elements, based on the reversible switching between the crystallized state and the glassy state of a chalcogenide layer, exhibiting a marked contrast in the optical reflectivity and electrical conductivity, can reveal T-material states to develop new types of neural networks.…”
Section: Introductionmentioning
confidence: 99%